RESPONSIVITAS DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN SUKOHARJO DALAM MENANGANI KELUHAN KERUSAKAN JALAN KABUPATEN SUKOHARJO - Nofitasari; Winduro, Wirid (Solidaritas, 2025)
The Public Works and Spatial Planning Department of Sukoharjo Regency is one of the public service agencies responsible for infrastructure, such as public roads. However, it still faces a number of problems when carrying out its duties. This can be seen from the many complaints or complaints from the public or criticism made by the public regarding the lack of response or action related to damage to district roads. Therefore, it is important to see how responsive the apparatus of the Public Works and Spatial Planning Department of Sukoharjo Regency is in handling public complaints so that the services provided are in accordance with what the public expects. The purpose of this study is to describe and analyze the responsiveness of the Public Works and Spatial Planning Department of Sukoharjo Regency in handling public complaints regarding road damage. The method used in the study is descriptive qualitative. The focus of the analysis in this study uses five indicators of responsiveness theory according to Agus Dwiyanto (2017), namely, the presence or absence of public complaints, the attitude of the meeting in responding to complaints, the use of complaints as a reference for improving services, the actions of officers to provide service satisfaction, and the placement of the community in the applicable service system. Data collection was carried out through observation, interviews, and documentation. The selection of informants was carried out using a purposive technique. While the data analysis technique used in this study was the Interactive Model data analysis from Miles Huberman and Saldana. The results of this study indicate that based on the five indicators of responsiveness according to Agus Dwiyanto's theory (2017), the responsiveness of the Public Works and Spatial Planning Agency of Sukoharjo Regency can be said to be unresponsive in handling complaints about damage to district roads, there are several things that are still obstacles in resolving them. This can be seen from the fact that not all public complaints can be responded to quickly because they have not been included in the budget agenda and the availability of a limited budget, then there are still obstacles that need to be optimized such as the lack of information about SOPs (Standard Operating Procedure) regarding the complaint flow and its handling. Keywords: Responsiveness, Complaints, Road Damage